An An Analysis of Pronunciation Errors in Speaking Of 2nd Semester Students of English Educate Department Universitas Bhinneka PGRI - Baiq Titis Lidyawaty; Ayu Rizki Septiana (Jurnal Pengabdian dan Pemberdayaan Masyarakat Kepulauan Riau (JPPM Kepri), 2021)
In this study, researchers will examine students' problems in pronunciation errors in English and the causes of students' errors in English pronunciation. This study aims to determine the pronunciation errors and the causes of errors in pronunciation made by students in speaking English. This research is descriptive qualitative research that aims to describe students' pronunciation errors and the causes of students' pronunciation errors. The subjects of this study were second-semester students of the English language study program at the University of Bhinneka PGRI. The reason the researcher chooses this subject is the first subject that the researcher wants to examine and understand because there are some students who experience pronunciation errors and the researcher wants to know where the pronunciation errors are and what causes make their pronunciation errors. Based on the results of observations, the researchers found that students' problems in speaking English were in the vowel they were stamped. The results of the questionnaire that the researchers distributed from the entire 2nd-semester class, both class 2A and class 2B, totaling 44 students, received answers from 39 students. The results obtained from 10 interviews researchers can conclude that there are several causes of difficulty or pronunciation errors in semester 2 students at the Universitas Bhinneka PGRI including Mother Language and Personality.